Getting a web development job for dummies - Taylor, Kathleen, 1953-; Smith, Bud E. (Hoboken, NJ : John Wiley, 2015)
Chart your path for a career in web development. Taylor and Smith help you start your career, by explaining the major categories of web development jobs, showing you how to position yourself for the job you want, and giving you advice on how to keep and grow within your ideal job once you've found it.
Includes index.
Keywords: Web site development industry -- Vocational guidance; Internet -- Vocational guidance; Job hunting; Internet -- History; Web site development